Assessment of component costs in residential building constructions in Metro Manila - Agojo, Mark Dave B.; Aquino, Sarah Chell A.
Cost is one of the most important factors that affects the overall success of a construction project. Having a correct early cost estimate is vital since it promotes efficiency in construction management standpoint, most especially in avoiding cost overruns. This study aims to assess the component cost percentage in typical residential building constructions in Metro Manila. The bills of materials collected were recategorized into the new proposed general format for bill of materials, tabulated and further analyzed using SPSS, a data analysis program that aids in determining the correlation of the cost percentages with the cost per unit area. The strength of linear associations of the identified components with the constTuction cost per unit area were analyzed. Results show that concreting works is the most dominant component in terms of cost allotment, followed by masonry works, with a combined 45-55% allotment across all types of residential structure. Also, most components exhibited moderate to strong linear relationship with construction cost per unit area. The construction cost survey is reliable to within +/- 6 percent at the 90% confidence interval for two-storey, single-dwelling residential buildings with roofing works. This research can be used in future studies such as predicting damage rating and assessment during post-calamities and providing more accurate cost estimates in residential building constructions. Also, results can be used in future works such as probabilistic risk assessment of correlation among cost components on the total cost variance of a construction project. Further recommendations were given in this study.